Depressive Symptom Network Associated With Comorbid Anxiety in Late-Life Depression - An, Min Ho; Park, Soon Sang; You, Seng Chan; Park, Rae Woong; Park, Bumhee; Woo, Hyung Kyoo; Kim, Han Ki; Son, Sang Joon (Frontiers in Psychiatry, 2019)
Background: Depression and anxiety are the most common comorbid psychiatric disorders in the elderly. Psychiatrists have been reporting worsened depression symptoms and prognosis by comorbid anxiety symptoms. However, it is still unclear how anxiety affects the course of depression in the elderly. The aims of this study are [1] to identify the symptom network in late-life depression (LLD), and [2] to examine the role of anxiety in LLD with a network perspective. Methods: The study analyzed 776 community-based participants who were clinically diagnosed with depression and enrolled in Suwon Geriatric Mental Health Center. Network analysis was used to investigate the relationships between the symptoms of Montgomery–Åsberg Depression Rating Scale (MADRS). Depression sample was divided into groups of low and high anxiety according to the Beck Anxiety Index. Propensity score matching (PSM) was used to minimize the effects of depression severity on the network. Network comparison test (NCT) were carried out to compare the global connectivity, global strength, and specific edge strength between the two subgroups. Results: Reported sadness, pessimistic thinking, and suicidal ideation are the core symptoms of LLD in terms of node strength. The MADRS sum score (mean [SD] 28.10 [9.19] vs 20.08 [7.11]; P < .01) were much higher in high anxiety group. The NCT before PSM showed high anxiety group had significantly higher global strength (P < .01). However, the NCT after PSM did not reveal any statistical significance both in global structure (P = .46) and global strength (P = .26). A comparison between centrality indices showed a higher node strength of vegetative symptoms in high anxiety group and it also remained after PSM. Conclusion: Based on the statistical analysis, anxiety worsens the severity of depression. However, NCT after PSM revealed comorbid anxiety does not change the global structure and strength of the depression symptom network. Therefore, anxiety may affect depression in a way of worsening the severity, rather than changing psychopathology. Additionally, the study revealed the centrality of vegetative symptoms was low in LLD but increased substantially in patients with comorbid anxiety.